Landscape‐level variability in historical disturbance in primary Picea abies mountain forests of the Eastern Carpathians, Romania. (2nd August 2013) - Svoboda, Miroslav; Janda, Pavel; Bače, Radek; Fraver, Shawn; Nagel, Thomas A.; Rejzek, Jan; Mikoláš, Martin; Douda, Jan; Boublík, Karel; Šamonil, Pavel; Čada, Vojtěch; Trotsiuk, Volodymyr; et al.
Abstract Questions How have the historical frequency and severity of natural disturbances in primary Picea abies forests varied at the forest stand and landscape level during recent centuries? Is there a relationship between physiographic attributes and historical patterns of disturbance severity in this system? Location Primary P. abies forests of the Eastern Carpathian Mountains, Romania; a region thought to hold the largest concentration of primary P. abies forests in Europe's temperate zone. Methods We used dendrochronological methods applied to many plots over a large area (132 plots representing six stands in two landscapes), thereby providing information at both stand and landscape levels. Evidence of past canopy disturbance was derived from two patterns of radial growth: (1) abrupt, sustained increases in growth (releases) and (2) rapid early growth rates (gap recruitment). These methods were augmented with non‐metric multidimensional scaling to facilitate the interpretation of factors influencing past disturbance. Results Of the two growth pattern criteria used to assess past disturbance, gap recruitment was the most common, representing 80% of disturbance evidence overall. Disturbance severities varied over the landscape, including stand‐replacing events, as well as low‐ and intermediate‐severity disturbances. More than half of the study plots experienced extreme‐severity disturbances at the plot level, although they were not always synchronized across stands and landscapes. Plots indicating high‐severity disturbances were often spatially clustered (indicating disturbances up to 20 ha), while this tendency was less clear for low‐ and moderate‐severity disturbances. Physiographic attributes such as altitude and land form were only weakly correlated with disturbance severity. Historical documents suggest windstorms as the primary disturbance agent, while the role of bark beetles (Ips typographus) remains unclear. Conclusions The historical disturbance regime revealed in this multi‐scale study is characterized by considerable spatial and temporal heterogeneity, which could be seen among plots within stands, among stands within landscapes and between the two landscapes. When the disturbance regime was evaluated at these larger scales, the entire range of disturbance severity was revealed within this landscape.